Problems of Atomic Science and Technology 2019
DOI: 10.46813/2019-123-105
|View full text |Cite
|
Sign up to set email alerts
|

FEATURES OF FORMATION OF CRYSTALLOGRAPHIC TEXTURE AND PROPERTIES IN Ti-3Al-2.5V TITANIUM ALLOY DURING TUBES MANUFACTURE

Abstract: Texture formation processes at all technological stages of tube manufacture were considered. It has been established that at the stage of hot deformation and manufacture of TREX tubes, tangential and radial textures are formed, a large share of tangential component of the texture. Influence of main factors of the technological process on formation of texture and properties was established. Conditions for formation of a maximum amount of radial texture in tubes which ensure improvement of service properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The previous texture study when rolling tubes at strains of 40...60% has shown that the share of radial texture did not exceed 45...49% [12] while requirements to it were not met often (it was at the level of 1-1.2). Besides, some tubes did not pass expansion and bending tests.…”
Section: The Study Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The previous texture study when rolling tubes at strains of 40...60% has shown that the share of radial texture did not exceed 45...49% [12] while requirements to it were not met often (it was at the level of 1-1.2). Besides, some tubes did not pass expansion and bending tests.…”
Section: The Study Resultsmentioning
confidence: 91%
“…Factor Q which reflects wall to diameter strain ratio [8] is indicator of these strains. Besides, overall strain degree, especially at last steps of tube manufacture plays an important role [9].…”
Section: The Study Resultsmentioning
confidence: 99%